Komunikasi Kristiani: Melawan Desakralisasi Diri di Media Sosial - Muni, Yanuarius (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2019)
Fake news spreads quickly and changes situations in the society. It has become a sort of linguistic violence circulating negative ideologies and perspectives that slowly destroy people both mentally and physically. The growing tendency of circulating fake news raises a serious problem in the society and moreover among Christians, for important human values, including religious values, are disregarded. Christian understanding of human beings as created in the image of God implies that they have the capacity to use good words to build a sacred society, that is, a society blessed by God. However, the tendency to retrieve and to disseminate information too quickly occurs almost automatically in this age of information, which ironically threatens every good intention of the self in building a trusting community. This article explores the elements of Christian communication based on the Church teachings on the subject matter, in order to counter the tendency of desacralisation of the self on social media and to promote truthful as well as deliberating communication in the society.